2014
DOI: 10.1002/anie.201408566
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Autoxidation Forms Highly Oxidized RO2 Radicals in the Atmosphere

Abstract: Gas-phase oxidation routes of biogenic emissions, mainly isoprene and monoterpenes, in the atmosphere are still the subject of intensive research with special attention being paid to the formation of aerosol constituents. This laboratory study shows that the most abundant monoterpenes (limonene and α-pinene) form highly oxidized RO2 radicals with up to 12 O atoms, along with related closed-shell products, within a few seconds after the initial attack of ozone or OH radicals. The overall process, an intramolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
366
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 235 publications
(401 citation statements)
references
References 19 publications
33
366
1
1
Order By: Relevance
“…We observed a consecutive formation of peroxy radicals, HOM monomer and dimer species, which is in agreement with previous studies conducted in both, a laminar flow tube and in a continuously stirred flow 5 reactor Jokinen et al, 2014). The simulated time evolution of the HOM followed the measured concentrations very precisely and the calculated yields from several experiments were in the range of 3.5-6.5%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed a consecutive formation of peroxy radicals, HOM monomer and dimer species, which is in agreement with previous studies conducted in both, a laminar flow tube and in a continuously stirred flow 5 reactor Jokinen et al, 2014). The simulated time evolution of the HOM followed the measured concentrations very precisely and the calculated yields from several experiments were in the range of 3.5-6.5%.…”
Section: Discussionsupporting
confidence: 91%
“…The selected dimer (C19H28O11) formation starts clearly later, which supports the hypothesis that it forms from reaction of two RO2 Jokinen et al, 2014). The carbon number 19 can be explained by loss of CO from RO2 (Jagiella et al, 2000;Rissanen et al, 2014), followed by reaction with a 10- …”
supporting
confidence: 75%
“…Importantly here, autoxidation steps which involve intramolecular H-atom abstraction from a C-H to an O-O bond and subsequent addition of O2 to reform a more oxidised RO2 radical do not generate HO2. Jokinen et al, (2014) observed a high formation rate of organic nitrates (of the order of 30%) when NO was added to experiments which would serve to further decrease RO2 to HO2 propagation. For ClearfLo conditions, a model run unconstrained to the mono-terpenes and the heavier-weight alkanes (MCM-VOC-STANDARD) under-estimated 10 OH reactivity (Whalley et al, 2016) with the missing OH reactivity fraction largely reconciled by the model-generated intermediates which derive from alpha-pinene and limonene.…”
Section: Uncertainties In the Model Chemistry Under Low No Conditionsmentioning
confidence: 95%
“…Phys. H-shift from C-H to an R-O-O bond and subsequent O2 additions (Crounse et al, 2011;Jokinen et al, 2014;Ehn et al, 2014;Berndt et al, 2016). Mass spectrometric signals relating to these highly oxidised RO2 species have also been observed during field measurements .…”
Section: Uncertainties In the Model Chemistry Under Low No Conditionsmentioning
confidence: 99%
“…8). Thus, the formation of the smallest clusters also seems to occur without solar radiation, which indicates that they may be formed, for example, by the low-volatile vapors produced in the ozonolysis of organic vapors Jokinen et al, 2014).…”
Section: Diurnal Variation Of Cluster Concentrations and Formation Ratesmentioning
confidence: 99%